Teacher training for using digital video camera in primary education - Pablo García Sempere (Universidad de Granada, 2011)
This paper shows the partial results of a research carried out in primary schools, which evaluates the ability of teachers in the use of digital video camera. The study took place in the province of Granada, Spain. Our purpose was to know the level of knowledge, interest, difficulties and training needs so as to improve the teaching practice. The work has been done from a descriptive and ecletic approach. Quantitative (questionnaire) and qualitative techniques (focus group) have been used in this research. The information obtained shows that most of the teachers have a lack of knowledge in the use of video camera and digital edition. On the other hand, the majority agrees to include initial and permanent training on this subject. Finally, the most important conclusions are presented.